2009
DOI: 10.1164/rccm.200808-1307oc
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Traffic-related Particles and Endotoxin during Infancy Is Associated with Wheezing at Age 3 Years

Abstract: Rationale: Murine models demonstrate a synergistic production of reactive oxygen species on coexposure to diesel exhaust particles and endotoxin. Objectives: It was hypothesized that coexposure to traffic-related particles and endotoxin would have an additive effect on persistent wheezing during early childhood. Methods: Persistent wheezing at age 36 months was assessed in the Cincinnati Childhood Allergy and Air Pollution Study, a high-risk birth cohort. A time-weighted average exposure to traffic-related par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
93
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 54 publications
(61 reference statements)
1
93
0
Order By: Relevance
“…11248 C. Xu et al: Fungi Diversity in PM 2.5 and PM 1 at the summit of Mt. Tai ris et al, 2002;Yadav et al, 2004;Bowers et al, 2012Bowers et al, , 2013Cao et al, 2014;Ryan et al, 2009). Despite their importance, the abundance, diversity, and community structure of fungi associated with PM have received limited attention in terms of research.…”
Section: Introductionmentioning
confidence: 99%
“…11248 C. Xu et al: Fungi Diversity in PM 2.5 and PM 1 at the summit of Mt. Tai ris et al, 2002;Yadav et al, 2004;Bowers et al, 2012Bowers et al, , 2013Cao et al, 2014;Ryan et al, 2009). Despite their importance, the abundance, diversity, and community structure of fungi associated with PM have received limited attention in terms of research.…”
Section: Introductionmentioning
confidence: 99%
“…Potential health risks of bioaerosols are especially high in urban environments due to their dense populations. Ryan et al (2009) reported that a combination of bioaerosols and traffic-related emission exposure was associated with wheezing at age 3 years. Bowers et al (2011) reported that the major bacteria sources in the urban environments are soil, leaf surfaces and dog feces.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, there is the Cincinnati Childhood Allergy and Air Pollution Study (CCAAPS) -a prospective birth cohort investigation (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) designed to determine if exposure to high levels of diesel exhaust particles (DEP) during early childhood increases the risk for developing allergic diseases. Resulting from the CCAAPS, wheezing, night cough and allergic rhinitis in infants residing in proximity to major roads and stop-and-go traffic was linked to exposure to elemental carbon attributable to traffic, which served as a marker for diesel exhaust particles (DEP) (Ryan et al, 2005(Ryan et al, , 2007(Ryan et al, , 2009Sucharew et al, 2010). Similar to other studies, CCAAPS relied on the aerosol exposure data measured in the tested metropolitan area over a specific period of time (beginning with the pilot study in 2001 and extending into a full-scale sampling in [2002][2003][2004][2005].…”
Section: Introductionmentioning
confidence: 99%
“…While OC is produced by all combustion sources, EC is primarily generated by traffic sources, largely by diesel-powered vehicles (Birch and Cary, 1996). As such, EC is frequently used as a surrogate for traffic generated aerosols (Holguin, 2008;Ryan et al, 2009;Hochstetler et al, 2011). The EC concentration and its contribution to PM 2.5 are greater in areas near highways and both increase with increased truck traffic (Kinney et al, 2000;Lena et al, 2002;Martuzevicius et al, 2004).…”
Section: Introductionmentioning
confidence: 99%